The colors of all the cattle [compact disc, unabridged] - McCall Smith, Alexander, 1948- (McCall Smith, Alexander, 1948- No. 1 Ladies' Detective Agency series (Recorded Books, Inc.)., 2018)
Mma Ramotswe reluctantly agrees to run for the city council when a developer announces plans to build a flashy hotel beside a graveyard, while Charlie volunteers to be the lead investigator in a case that lands him in hot water.